Persepsi Pasien Terhadap Kualitas Pelayanan Kefarmasian Di Apotek Salam Sarma Kota Pangkalpinang Tahun 2024 - Delvy Anggreini; Eva Dewi Rosmawati Purba; Mirnawati Zalili Sailan (PT Bukuloka Literasi Bangsa, 2025)
Perception is a process by which an individual interprets their sensory impressions to assign meaning or evaluate the quality of the services received, including in pharmacies as pharmaceutical services facilities. Salam Sarma Pharmacy is a private pharmacy and clinic strategically located in the city center, open 24 hours and offering general practitioner, dentist, specialist doctor services and a circumcision center. Preliminary study results show the number of visits in 2022 and 2023. In 2022, there were 25,368 patient visits and in 2023, there were 23,588 patient visits. The represents a decrease of 1,780 patient visits. To measure patients' perception of the quality of pharmaceutical services at Salam Sarma Pharmacy in Pangkalpinang City in 2024, the Service Quality (SERVQUAL) method is used. This research is a survey study using a descriptive research method with a prospective study. The sampling technique used is non-random sampling with an accidental sampling method, and a questionnaire is used as the data collection tool. The data analysis in this research is univariate analysis. There are 5 SERVQUAL dimensions with an overall average value of 3.44, where in the reliability dimension the average value is 3.40, the responsiveness dimension has an average value of 3.44, the assurance dimension has an average value of 3.47, the empathy with an average value of 3.40 and the tangibles dimension with an average value of 3.40. Overall, the patients' perception of the quality of pharmaceutical services at Salam Sarma Pharmacy in Pangkalpinang City in 2024 is categorized as very good. Keywords: Perception, Service Quality